2017
DOI: 10.1080/15384101.2016.1256149
|View full text |Cite
|
Sign up to set email alerts
|

New ideas connecting the cell cycle and pancreatic endocrine-lineage specification

Abstract: Neurogenin 3 (Neurog3) is a pro-endocrine transcription factor required for endocrine-lineage specification during mouse pancreas development. It was a long-standing notion that Neurog3 activation in Sox9 C epithelial cells, a subset of early multipotent progenitors that produce ductal and endocrine lineages, triggers a rapid progression to a post-mitotic, Neurog3 HI endocrine-committed precursor state. We challenged this model by demonstrating that a mitotic progenitor state, in which Neurog3 is transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
3
2
0
Order By: Relevance
“…These findings support our model that, in actively cycling Neurog3 TA.LO progenitors, Neurog3 protein levels vary according to the cell-cycle phase (Bechard and Wright, 2017). To address this issue, we used Neurog3 P2A.FUCCI reporter expression in Neurog3 TA.LO progenitors to track cell-cycle progression in relation to Neurog3 protein levels.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These findings support our model that, in actively cycling Neurog3 TA.LO progenitors, Neurog3 protein levels vary according to the cell-cycle phase (Bechard and Wright, 2017). To address this issue, we used Neurog3 P2A.FUCCI reporter expression in Neurog3 TA.LO progenitors to track cell-cycle progression in relation to Neurog3 protein levels.…”
Section: Resultssupporting
confidence: 89%
“…These findings support our model that, in actively cycling Neurog3 TA.LO progenitors, Neurog3 protein levels vary according to the cell-cycle phase (Bechard & Wright, 2017 (30/120) (Figure 3a).…”
Section: Neurog3 Levels and Progenitor Maintenance Vs Endocrine-cosupporting
confidence: 89%
See 1 more Smart Citation
“…Recent studies showed that during S-G 2 -M, Neurog3 is kept in a hyperphosphorylated unstable state via Cdk phosphorylation, and that decreased Cdk activity associated with entrance into G 1 result in stabilization and accumulation ( 14 , 15 ). These findings support our model that, in actively cycling Neurog3 TA.LO progenitors, Neurog3 protein levels vary according to the cell-cycle phase ( 13 ). To address this issue, we used Neurog3 P2A.FUCCI reporter expression in Neurog3 TA.LO progenitors to track cell-cycle progression in relation to Neurog3 protein levels.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, time-lapse observations show that the transition from the low level of Neurog3 observed in mitotic Neurog3 TA.LO progenitors to the high level necessary for endocrine-commitment occurs ~3-6 hours after division of the parental Neurog3 TA.LO cell, during G 1 ( 6 ). These findings led to our proposal that the level and stability of Neurog3 in mitotic Sox9 + Neurog3 TA.LO progenitors is regulated by the cell cycle and that G 1 extension promotes Neurog3 stabilization, accumulation, and endocrine commitment ( 13 ). Two recent reports support this model, demonstrating that Neurog3 is targeted and destabilized by Cdks and that G 1 lengthening, by reducing Cdk activity, causes the accumulation of a more stable un(der)phosphorylated form of Neurog3 ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%